ON THE STAR CHAINS AROUND THE GALACTIC CLUSTER NGC 2244 - PISMIS, P (UNAM, Observatorio Astronómico Nacional, CD MEXICO, DF, MEX, 1954)
Our program on the study of the galactic clusters and their surrounding using plates taken with the Tonantzintla Schmidt telescope, includes among other nebulous cluster, also NGC 2244. This object is immersed in the so called Rosette Nebula. The galactic
BOL OBS TONAN TACUB
Keywords: STAR CHAINS, AROUND, GALACTIC, CLUSTER; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; ESTRELLAS